An Analysis of Al-Qur’an Language as a Mediator for Politicization of Religion in Indonesia - Mohammad Makinuddin (UIN Sunan Kalijaga Yogyakarta, 2021)
This study is conducted to comprehend the politicization of religion typology based on the use of Al-Qur’an language on the narrative of the politic in Indonesia. The politicization of religion is a widespread phenomenon among Indonesian people. Some political events in Indonesia cannot be separated from religious symbols, for example, conveying Al-Qur’an theorems to spread political agendas. Al-Qur’an, its communicative language characteristics, is frequently used as a mediator to spread particular narratives for power. This study uses a qualitative approach by gathering contents or narratives related to Al-Qur’an verses for a political power struggle in Indonesia. This study uses the linguistic method to see how the discourses of Al-Qur’an as a language of religion become a tool to build a social identity related to politics. The result of this study shows that Al-Qur’an can be a mediator in the spread of political narratives. Besides, the characteristics of the Al-Qur’an language, which tend to have communicative feel, can potentially be used as a political communication tool. This study has a contribution toward the development of politicization of religion typology through the Al-Qur’an language. Al-Qur’an and its user have a connection with various discourses and debates in particular contexts. Therefore, to comprehend an interpretation, it is essential to see the context and society's need when analysing a text.